Das Wiener Stadtzeichnerbuch 1678-1685 Ein Bettlerverzeichnis aus einer frühneuzeitlichen Stadt - Pichlkastner, Sarah (2014)
Poverty and beggars have always been a part of the city of Vienna. Between 1443 and 1693 only beggars with beggars' badges ("Stadtzeichen") were authorised to beg. The contextualisation, edition and analysis of a beggars' directory ("Stadtzeichnerbuch") dating from the seventeenth century (1678-1685) reveals the living circumstances of more than 900 poor people which can hardly be found in other sources.